A Hydraulic Comparison between Center Pivot Irrigation Traditional and Modern Type ANABIB - Hadji Mohammed Salah; Guerrah Ayoub; Mansouri Khaled (University of Eloued, 2019)
The objective of this article is to realize a hydraulic comparison between the traditional and modern irrigation pivot system (Type ANABIB). This comparison is based on evolution of hydraulic parameters like pressure, flow and length between the sprinklers (nozzles) to obtain a homogeneous distribution of water over the entire irrigated area. Center Pivot irrigation has an important agricultural component in Algeria, especially in the South such (El Oued, Ouargla, Biskra, Meniaa, Adrar, etc.). However, this irrigation technique is often used by farmers, who don’t have the scientific expertise to develop and improve the performance of their equipment, taking into account the weather conditions of desert areas, as well as the sizing of the pumping system. Farmers in Souf deal with the traditional pivot system and don’t accept the modern type ANABIB with suitable normalization factor because its high cost. Therefore, the necessity to improve hydraulic performance of the traditional system until it has a high normalization factor and good uniformity of irrigation. However in well-designed devices we can get a good hydraulic efficiency the order of 85%. The results of the work observed for the hydraulic parameters of traditional system commonly used by farmers give us 59,58 and 70,76% of Cuh that values gives us the possibility to improve its uniformity of irrigation by the predominant effect of the sprinkler distance to get an acceptable values of normalization factor (over than 85%), on the other hand ANABIB system gives 95,98 and 97,28% of Cuh that considers as a perfect values . It is intended that this article be served as a starting point from which improved uniformity may be developed in the future
Intervention
Keywords: Hydraulic performance; nozzles; pumping system; irrigation system